Long-Term Experimental Evaluation of Software Aging Effects in NoSQL Database - Amaral, Paulo; Araujo, Jean (Anais do Latin-American Symposium on Dependable Computing (LADC); 2025: Anais do XIV Latin-American Symposium on Dependable Computing, 2025)
The increasing reliance on NoSQL databases in cloud-native and data-intensive applications raises concerns about their long-term dependability. Software aging is a phenomenon that leads to performance degradation or increased failure rates in long-running systems. Although few studies have investigated the effects of aging in relational Database Management Systems (DBMSs), even less attention has been given to NoSQL systems. To address this gap, this paper presents, to the best of our knowledge, the first long-term experimental investigation of software aging in MongoDB NoSQL database. We also introduce the approach called SWCycles, which accelerates aging manifestation through repeated stress-wait cycles. The experiment performed continuous read operations using 500 concurrent virtual users during 48-hour stress periods and 6 wait hours, repeating over a total span of 63.25 d. Memory usage was continuously monitored, and the collected data were analyzed using the Mann-Kendall trend test. The results indicated a statistically significant upward trend in RAM consumption, suggesting the occurrence of memory leaks and fragmentation. Using Kendall-Theil regression, we estimate system failure due to memory exhaustion, after the completion of each stress-wait cycle.